Carcinosarcoma of the maxillary sinus: a rare case report - Subha, Sethu Thakachy; Doi, Mohamad; Mohd Yatim, Nor Yatizah (Iranian Pediatric Hematology and Oncology Society, 2020)
Carcinosarcoma is a highly malignant tumour exhibiting histological components of both carcinomatous and sarcomatoid elements. Carcinosarcoma is extremely rare in the sinonasal cavity. Due to the rarity and clinical diversity, these neoplasms are often misdiagnosed and pose a challenge in their management. Here we report a 44-year-old man with epistaxis and progressive symptoms of nasal obstruction. Nasal endoscopy revealed a polypoid mass in right middle meatus extending into the nasal cavity. Polypectomy through endoscopic sinus surgery was performed. Carcinosarcoma was diagnosed based on histopathology and immunohistochemical studies. The patient underwent total maxillectomy followed by radiotherapy for the residual tumor. Unfortunately, the patient suffered from multiple recurrences during 20 months following primary resection. This report is to emphasize the need for early diagnosis and radical multimodality intervention for this rare malignancy with an ominous prognosis.